Evaluation of Different Advanced Approaches to Simulation of Dynamic In Vitro Digestion of Polyphenols from Different Food Matrices-A Systematic Review - Carmen Duque-Soto; Alejandra Quintriqueo-Cid; Ascensión Rueda-Robles; Paz Robert; Isabel Borrás-Linares; Jesús Lozano-Sánchez (MDPI AG, 2022)
Phenolic compounds have become interesting bioactive antioxidant compounds with implications for obesity, cancer and inflammatory gastrointestinal pathologies. As the influence of digestion and gut microbiota on antioxidant behavior is yet to be completely elucidated, and due to limitations associated to in vivo studies, dynamic in vitro gastrointestinal models have been promoted. A systematic review was conducted of different databases (PubMed, Web of Science and Scopus) following PRISMA guidelines to assess different dynamic digestion models and assay protocols used for phenolic compound research regarding bioaccesibility and interaction with colonic microbiota. Of 284 records identified, those including dynamic multicompartmental digestion models for the study of phenolic compound bioaccesibility, bioactivity and the effects of microbiota were included, with 57 studies meeting the inclusion criteria. Different conditions and experimental configurations as well as administered doses, sample treatments and microbiological assays of dynamic digestion studies on polyphenols were recorded and compared to establish their relevance for the dynamic in vitro digestion of phenolic compounds. While similarities were observed in certain experimental areas, a high variability was found in others, such as administered doses. A description of considerations on the study of the digestion of phenolic compounds is proposed to enhance comparability in research.